Evaluation of a Loop-Mediated Isothermal Amplification Assay to Detect Carbapenemases Directly From Bronchoalveolar Lavage Fluid Spiked With Acinetobacter spp. - Moreno-Morales, Javier; Vergara, Andrea; Kostyanev, Tomislav; Rodriguez-Baño, Jesús; Goossens, Herman; Vila, Jordi (Frontiers in Microbiology, 2021)
Carbapenem-resistant Acinetobacter spp. mainly Acinetobacter baumannii are frequently causing nosocomial infections with high mortality. In this study, the efficacy of the Eazyplex® SuperBug Complete A system, based on loop-mediated isothermal amplification (LAMP), to detect the presence of carbapenemases in Acinetobacter spp. directly from bronchoalveolar lavage (BAL) samples was assessed. A total of 22 Acinetobacter spp. strains producing OXA-23, OXA-40, OXA-58, NDM, and IMP were selected. Eazyplex SuperBug Complete A kit, used with the Genie II device, is a molecular diagnostics kit that detects a selection of genes that express carbapenemases (blaKPC, blaNDM, blaVIM, blaOXA–48, blaOXA–23, blaOXA–40, and blaOXA–58). Negative BAL samples were identified, McFarland solutions were prepared from each of the 22 Acinetobacter strains and serial dilutions in saline solution were made to finally spike BAL samples to a concentration of 102 and 103 CFU/ml. Fifteen concentrations out of the 44 tested out did not provide detection of the carbapenemase-producing gene, all but one being at the lowest concentration tested at 102 CFU/ml; therefore, the limit of sensitivity is 103 CFU/ml. This assay represents the kind of advantages that investing in molecular diagnostics brings to the clinical practice, allowing the identification of carbapenemases in less than 30 min with a sensitivity of 103 CFU/ml.